The Influence of Communication, Training, and Organizational Culture on Employee Performance - Syahruddin, Syahruddin; Hermanto, Hermanto; Wardini, Amalia Kusuma (Jurnal Organisasi dan Manajemen, 2020)
This study aims to determine the influence of communication, training, and organizational culture on employee performance. The Slovin formula was used to select 69 respondents out of a total of 105 employees of the Office of the Ministry of Religion of the City of Bima for the study. Data were obtained through questionnaires and analyzed using the multiple linear regression method. Findings. The results showed that communication, training, and organizational culture significantly and positively influenced employee performance. Furthermore, the result showed that organizational culture is the most dominant variable that influences employee performance, followed by training and communication. This means that to improve employee performance, it is important to pay attention to building an organizational culture that supports each task implementation, by taking into account communication patterns and involving all employees in training programs that can improve their work competence.